Burundi : Fifth Review Under the Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of a Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Fifth Review Under the Poverty Reduction and Growth Facility (PRGF) Arrangement for Burundi. Macroeconomic performance under the PRGF-supported program in 2006 was broadly in line with the program. All end-June and end-September 2006 quantitative performance targets were met with the exception of a temporary accumulation of external arrears. Structural reforms lagged in mid-2006. The structural performance criterion at end-September and the structural benchmarks were missed. The measures covered by the performance criterion and three of the benchmarks were implemented by early 2007.